2013
DOI: 10.1007/s00784-013-0952-0
|View full text |Cite
|
Sign up to set email alerts
|

The potential association between gingival crevicular fluid inflammatory mediators and adverse pregnancy outcomes: a systematic review

Abstract: The present findings suggest that an association between GCF inflammatory mediator levels and APO might exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 49 publications
(98 reference statements)
0
18
0
Order By: Relevance
“…Moreover, GCF levels of IL‐8, CRP, and IL‐1β were lower in cases compared to controls, which is discordant with the present findings. A systematic review on the relation between periodontal inflammation and adverse pregnancy outcomes concluded that there is an association between GCF inflammatory mediators and preterm birth 36 . However, because of great heterogeneity in the designs of reported studies, it was suggested that that association requires further confirmation and clarification through studies with a more systematic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GCF levels of IL‐8, CRP, and IL‐1β were lower in cases compared to controls, which is discordant with the present findings. A systematic review on the relation between periodontal inflammation and adverse pregnancy outcomes concluded that there is an association between GCF inflammatory mediators and preterm birth 36 . However, because of great heterogeneity in the designs of reported studies, it was suggested that that association requires further confirmation and clarification through studies with a more systematic approach.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of serum and amniotic fluid inflammatory mediators were associated with APO, especially PTB . A systematic review reported a positive association between APO and inflammatory mediator levels in gingival crevicular fluid, which is an inflammatory exudate from the gingival margin or within the gingival crevice . According to the above result, systemic inflammatory status caused by periodontal diseases might induce local inflammatory responses in the feto‐placental unit to increase the occurrence of APO.…”
Section: Inflammatory Mediators Produced By Gingival Submucosamentioning
confidence: 97%
“…23 Although it has been asserted that periodontopathogens from oral infection can disseminate to distant body sites and thus result in the delivery of PLBW infants, results have been inconclusive. 24,25,26,27 Some studies have demonstrated positive correlations, while others have not. 28,29,30,31,32,33,34,35 Although these results seem contradictory, factors such as race, geographical location, and socioeconomic standards have not been adequately adjusted for.…”
Section: Discussionmentioning
confidence: 99%